2020
DOI: 10.15406/emij.2020.08.00286
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and endocrinology – intersections: a review of current knowledge on physiopathological associations

Abstract: Introduction: The coronavirus-19 pandemic has reached historic dissemination, with a huge impact on physical, social and psychological well-being; understanding the pathophysiology of the disease is extremely important, as it can lead to effective therapy formulations. Objective: In this review, we will explore the current evidence surrounding the interactions of endocrine conditions and possible treatment targets. Methods: we reviewed the Medline, EMBASE and LiLACS databases using the keywords "COVID-19" or "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The clinical course of COVID-19 is often unpredictable and is characterized by oligosymptomatic forms of the disease, presenting itself as an asymptomatic or mild case (30-60%) to a moderate or severe/critical case, which is often characterized by pneumonia (6%). 25 In this study, 16.67% of the patients diagnosed with COVID-19 were asymptomatic. This study showed symptomatic COVID-19 patients to be frequently associated with the presence of multiple symptoms at presentation (29.63-37.96%), including fever (52.78%), dry cough (46.30%), myalgia (36.11%), headache (22.22%) and rhinorrhea (15.74%) as chief clinical complaints.…”
Section: Discussionmentioning
confidence: 59%
“…The clinical course of COVID-19 is often unpredictable and is characterized by oligosymptomatic forms of the disease, presenting itself as an asymptomatic or mild case (30-60%) to a moderate or severe/critical case, which is often characterized by pneumonia (6%). 25 In this study, 16.67% of the patients diagnosed with COVID-19 were asymptomatic. This study showed symptomatic COVID-19 patients to be frequently associated with the presence of multiple symptoms at presentation (29.63-37.96%), including fever (52.78%), dry cough (46.30%), myalgia (36.11%), headache (22.22%) and rhinorrhea (15.74%) as chief clinical complaints.…”
Section: Discussionmentioning
confidence: 59%
“…All age groups may be affected by COVID-19 infection. The disease is more severe in men ( 6 , 18 ). Older subjects (> 65 years), black subjects, smokers, and subjects with immunodeficiency, cardiac and respiratory diseases, cancer, hypertension, diabetes, obesity, and dyslipidemia are considered high-risk populations ( 13 , 19 ).…”
Section: Covid-19 Infectionmentioning
confidence: 99%
“…With higher adiposity commonly associated with type 2 diabetes, more receptors (ACE2) are available for SARS-CoV-2, exposing subjects to COVID-19 infection. In addition, subjects with excess adiposity may experience a more serious COVID-19 infection through several mechanisms (e.g., inflammation, impaired immunity, mechanical lung dysfunction, impact of comorbidities, and vitamin D deficiency) ( 5 , 7 , 15 , 16 , 18 , 19 , 28 31 ).…”
Section: Impact Of Diabetes On Covid-19 Infectionmentioning
confidence: 99%
“…Men with COVID-19 are exposed to worse outcome than women, possibly due to sex differences in immune response [11,12].…”
Section: Testismentioning
confidence: 99%
“…Vitamins are important in the prevention of viral infection. Subjects at risk of or with respiratory viral infection should receive vitamin C and vitamin D. Particular attention should be paid to the treatment of subjects with hypovitaminosis D [8,11,12].…”
Section: Nutrition (Calories Macronutrients Electrolytes Vitamins) and Exercisementioning
confidence: 99%